Abnormal scaffold attachment factor 1 expression and localization in spinocerebellar ataxias and Huntington's chorea. (13th July 2020) - Buckner, Nicola; Kemp, Kevin C.; Scott, Helen L.; Shi, Gongyu; Rivers, Caroline; Gialeli, Andriana; Wong, Liang-Fong; Cordero-LLana, Oscar; Allen, Nicholas; Wilkins, Alastair; Uney, James B.
Abstract: SAFB1 is a DNA and RNA binding protein that is highly expressed in the cerebellum and hippocampus and is involved in the processing of coding and non‐coding RNAs, splicing and dendritic function. We analyzed SAFB1 expression in the post‐mortem brain tissue of spinocerebellar ataxia (SCA), Huntington's disease (HD), Multiple sclerosis (MS), Parkinson's disease patients and controls. In SCA cases, the expression of SAFB1 in the nucleus was increased and there was abnormal and extensive expression in the cytoplasm where it co‐localized with the markers of Purkinje cell injury. Significantly, no SAFB1 expression was found in the cerebellar neurons of the dentate nucleus in control or MS patients; however, in SCA patients, SAFB1 expression was increased significantly in both the nucleus and cytoplasm of dentate neurons. In HD, we found that SAFB1 expression was increased in the nucleus and cytoplasm of striatal neurons; however, there was no SAFB1 staining in the striatal neurons of controls. In PD substantia nigra, we did not see any changes in neuronal SAFB1 expression. iCLIP analysis found that SAFB1 crosslink sites within ATXN1 RNA were adjacent to the start and within the glutamine repeat sequence. Further investigation found increased binding of SAFB1 to pathogenic ATXN1‐85Q mRNA. These novel data strongly suggest SAFB1 contributes to the etiology of SCA and Huntington's chorea and that it may be a pathological marker of polyglutamine repeat expansion diseases.